English phonetics and phonology : an introduction - Carr, Philip , 1953- (Wiley-Blackwell, 2013)
The second edition of the popular English Phonetics and Phonology textbook has been extensively updated and expanded to offer greater flexibility for teachers and increased support for non-native speakers studying the sound systems of English